The key to increasing competitiveness is investing into human resources - Csath, Magdolna (Studia Mundi – Economica, 2018)
This paper focuses attention on the fact that the V4 (Visegrád) countries are not equally well prepared to capitalize on the opportunities offered by the fourth industrial revolution because of the differences in the quality and skills of their human resources. On top of this they lag behind the more developed competitor countries in Western Europe in almost all major human indicators. Nine indicators describing human and knowledge characteristics are analyzed for the V4 and 5 developed countries.In some cases Poland stands out with a slightly better result, but together as a group the V4 countries lag behind for all the analyzed indicators compared to the 5 developed countries. Figure 10 which summarizes the results of 5 key indicators proves this problem. The article ends by suggesting that unless the V4 countries start putting stronger emphasis on developing human and knowledge resources they will lose a historic opportunity for becoming a successful actor in the ongoing processes of the fourth industrial revolution.
Keywords: Fourth industrial revolution; human resources; intangibles; education; life-long learning